An Analysis of the Implementation of Village Fund Policy Management in Pakembinangun Village, Pakem District, Sleman Regency - Imam, Sadrul; Muhaimin, Muhaimin (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
The implementation of the village fund policy refers to the allocation of financial resources originating from the State Budget (APBN), designated for villages and customary village entities, which are distributed through Regional Budgets (APBD) to regencies and municipalities. These funds are intended to finance governmental operations, infrastructure development, community empowerment, and sociocultural facilitation. With the enactment of Law Number 6 of 2014 concerning Villages, villages are restored as entities with community-endowed rights, thus establishing village autonomy in which governance is conducted independently, by and for the people. Consequently, all administrators and stakeholders of village development are expected to exhibit independence, proactiveness, and cooperation. The management of village finances encompasses a comprehensive system consisting of planning, implementation, administration, reporting, and financial oversight. This study adopts a descriptive qualitative approach, with data gathered in the form of narratives and visuals rather than numerical statistics. The existence of various phenomena indicates significant deficiencies in the governance and accountability mechanisms related to village fund utilization. These shortcomings have escalated the demand for improved financial responsibility, not only from village authorities but also from the local community. Accordingly, this study seeks to critically examine the accountability practices of village governments. The case of Pakembinangun Village in Pakem District, Sleman Regency, exemplifies such challenges, notably in the form of suboptimal fund absorption rates and discrepancies between budget allocations and actual expenditures